Unbound voices : a documentary history of Chinese women in San Francisco - Yung, Judy (University of California Press, 1999)
Unbound Voices brings together the voices of Chinese American women in a fascinating, intimate collection of documents--letters, essays, poems, autobiographies, speeches, testimonials, and oral histories--detailing half a century of their lives in America. Together, these sources provide a captivating mosaic of Chinese women's experiences in their own words, as they tell of making a home for themselves and their families in San Francisco from the Gold Rush years through World War II.
Keywords: Chinese American women -- California -- San Francisco -- History -- Sources.; Chinese American women -- California -- San Francisco -- Social conditions -- Sources.; Women immigrants -- California -- San Francisco -- History -- Sources.; Chinese American women -- California -- San Francisco -- Biography.; San Francisco (Calif.) -- Social conditions -- Sources.; San Francisco (Calif.) -- Ethnic relations -- Sources.; Américaines d'origine chinoise -- Californie -- San Francisco -- Histoire -- Sources.; Américaines d'origine chinoise -- Californie -- San Francisco -- Conditions sociales -- Sources.; Immigrantes -- Californie -- San Francisco -- Histoire -- Sources.; Américaines d'origine chinoise -- Californie -- San Francisco -- Biographies.; HISTORY -- State & Local -- General.; HISTORY / United States / State & Local / West (AK, CA, CO, HI, ID, MT, NV, UT, WY); Chinese American women; Chinese American women -- Social conditions; Ethnic relations; Social conditions; Women immigrants; California -- San Francisco; Chinezen.; Vrouwen.; Chinese American women -- California -- San Francisco -- History.; Chinese American women -- California -- San Francisco -- Social conditions.; Chinese -- California -- San Francisco.; United States, California, San Francisco, San Francisco -- Minorities.; Chinoises -- Californie (États-Unis) -- San Francisco (Calif.) -- Histoire -- Sources.; Chinoises -- Californie (États-Unis) -- San Francisco -- Conditions sociales -- Sources.; Immigrées -- Californie (États-Unis) -- San Francisco -- Histoire.; Chinoises -- Californie (États-Unis) -- San Francisco -- Biographie.; San Francisco (Calif.) -- Conditions sociales -- Sources.; San Francisco (Calif.) -- Relations interethniques -- Sources.; Biographies; History; Sources; Biographies.